Cálculo da Frequência Instantânea Cardíaca Utilizando o Algoritmo LMS e uma Interface de Aquisição de Dados - Brito, Deusdete de Sousa (2002)
In this work we consider the calculation of the heart instantaneous frequency from the estimate of the weights, gotten through LMS algorithm, (Least Mean Squares) when functioning as spectrum analyzer. It is known that the electrocardiogram (ECG) is a signal that is characterized for a repetitive regularity, which can be called quasi-periodicity. We explore this characteristic to extract the instantaneous frequency of the referred signal. For this, we use the LMS as a spectral analyzer. We use as reference inputs pairs of sines and cosines, inside the frequency band where if it finds the frequency of the desired signal, namely, the heart frequency. The algorithm estimates the frequency desired in real time, with the signal acquired through a data acquisition interface Intel 80C31. The results obtained show that the algorithm can be recommended for this purpose, as besides being easily implemented and generating small computational load it estimates the heart instantaneous frequency with a relative mean error of 0.025 which represent a difference of 18.89% between the two methods.